2019
DOI: 10.1007/s10902-019-00198-4
|View full text |Cite
|
Sign up to set email alerts
|

A Pecuniary Explanation for the Heterogeneous Effects of Unemployment on Happiness

Abstract: Why unemployment has heterogeneous effects on subjective well-being remains a hot topic. Using German Socio-Economic Panel data, this paper finds significant heterogeneity using different material deprivation measures. Unemployed individuals who do not suffer from material deprivation may not experience a life satisfaction decrease and may even experience a life satisfaction increase. Policy implications for taxation and unemployment insurance are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
1
4
0
2
Order By: Relevance
“…We pursued additional analyses to investigate the hypothesized mediation of financial satisfaction, satisfaction with time use, and time pressure. These analyses confirm previous findings (Luo, 2020) in showing that financial satisfaction mediates the relationship between unemployment and life satisfaction. A new finding is that financial satisfaction mediates the relationship with emotional well-being, either directly, presumably by decreasing stress and insecurity (Hiswåls et al, 2017), or indirectly through satisfaction with time use, presumably by giving access to economic means necessary for engagement in enjoyable free-time activities (Kahneman & Deaton, 2010;Killingsworth, 2021;Kushlev et al, 2015;Whillans et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We pursued additional analyses to investigate the hypothesized mediation of financial satisfaction, satisfaction with time use, and time pressure. These analyses confirm previous findings (Luo, 2020) in showing that financial satisfaction mediates the relationship between unemployment and life satisfaction. A new finding is that financial satisfaction mediates the relationship with emotional well-being, either directly, presumably by decreasing stress and insecurity (Hiswåls et al, 2017), or indirectly through satisfaction with time use, presumably by giving access to economic means necessary for engagement in enjoyable free-time activities (Kahneman & Deaton, 2010;Killingsworth, 2021;Kushlev et al, 2015;Whillans et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Hence, a difference in judgments of life satisfaction is expected between the employed and unemployed (Knabe et al, 2010). Previous studies (Ervasti & Venetoklis, 2010;Luo, 2020) have shown that both perceived financial strain and financial satisfaction (i.e., satisfaction with the personal economy) partially mediates the relationship between unemployment and life satisfaction. Our first hypothesis (H1a) is that, as found previously, financial satisfaction is a mediator of the relationship between life satisfaction and unemployment.…”
Section: Introductionmentioning
confidence: 96%
“…The results did not change when we excluded the effect sizes based on standardized regression coefficients (M1b). However, when we omitted two studies (Luo, 2020;Van Hoorn & Maseland, 2013) given their disproportionate sample and effect sizes, the population mean difference slightly increased to −.38 (M1a).…”
Section: Resultsmentioning
confidence: 97%
“…Countries characterized by high levels of employment protection showed a small meta-analytic mean difference (δ = −.10) when compared to countries with low levels (δ = −.42). However, these differences disappeared when we re-ran the analyses after the exclusion of two studies with large sample and effect sizes (Luo, 2020;Oesch & Lipps, 2013;see M16a and M17a). Since these latter results may be an indication of the two studies' dominating effect biasing estimations, for interpretation and comparison purposes, we relied on the meta-analytic effect sizes produced by the exclusion of the two studies.…”
Section: Country-level Factorsmentioning
confidence: 98%
“…(S03)). S druge strane, neki od sudionika istaknuli su da imaju više vremena za druge aktivnosti ("Ja, ja ne znam šta znači ustat' se ujutro u 5 sati… Boli me briga, spavam dokad hoću Luo (2019…”
unclassified